Helicobacter pylori in the Indonesian Malay’s descendants might be imported from other ethnicities - Ari Fahrial Syam (Gut Pathogens, 2021)
Abstract Background Even though the incidence of H. pylori infection among Malays in the Malay Peninsula is low, we observed a high H. pylori prevalence in Sumatra, which is the main residence of Indonesian Malays. H. pylori prevalence among Indonesian Malay descendants was investigated. Results Using a combination of five tests, 232 recruited participants were tested for H- pylori and participants were considered positive if at least one test positive. The results showed that the overall H. pylori prevalence was 17.2%. Participants were then categorized into Malay (Aceh, Malay, and Minang), Java (Javanese and Sundanese), Nias, and Bataknese groups. The prevalence of H. pylori was very low among the Malay group (2.8%) and no H. pylori was observed among the Aceh. Similarly, no H. pylori was observed among the Java group. However, the prevalence of H. pylori was high among the Bataknese (52.2%) and moderate among the Nias (6.1%). Multilocus sequence typing showed that H. pylori in Indonesian Malays classified as hpEastAsia with a subpopulation of hspMaori, suggesting that the isolated H. pylori were not a specific Malays H. pylori. Conclusions Even though the ethnic groups live together as a community, we observed an extremely low H. pylori infection rate among Indonesian Malay descendants with no specific Indonesian Malay H. pylori. The results suggest that H. pylori was not originally among these groups and H. pylori was imported from other ethnic groups.